2018
DOI: 10.1103/physrevb.98.054308
|View full text |Cite
|
Sign up to set email alerts
|

Modification of relaxation dynamics in Tb3+:Y3Al5O12 nanopowders

Abstract: Nanostructured rare-earth-ion doped materials are increasingly being investigated for on-chip implementations of quantum information processing protocols as well as commercial applications such as fluorescent lighting. However, achieving high-quality and optimized materials at the nanoscale is still challenging. Here we present a detailed study into the restriction of phonon processes in the transition from bulk crystals to small (≤ 40 nm) nanocrystals by observing the relaxation dynamics between crystal-field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In contrast to REI doped bulk materials, powders offer low cost and rapid prototyping. Furthermore, the understanding of powders constitutes a first step towards nanofabrication of devices from these materials [4][5][6][7]. However, despite much effort [8][9][10][11], producing monodisperse powders with properties comparable to those of bulk materials remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to REI doped bulk materials, powders offer low cost and rapid prototyping. Furthermore, the understanding of powders constitutes a first step towards nanofabrication of devices from these materials [4][5][6][7]. However, despite much effort [8][9][10][11], producing monodisperse powders with properties comparable to those of bulk materials remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Very high quality materials are therefore needed to reach T 2 values comparable to bulk samples. In this sense, Eu 3+ doped Y 2 O 3 is a particularly interesting candidate: in contrast to other RE materials, 27,[32][33][34] Eu 3+ doped Y 2 O 3 nanoparticles presenting remarkable optical and spin coherence properties, as well as narrow size distribution and bulk-like optical absorption and emission features can be obtained by chemical synthesis. [35][36][37] Our previous studies on Eu 3+ :Y 2 O 3 nanoparticles synthesized by homogeneous precipitation demonstrated an optical homogeneous linewidth of 45 kHz (T 2 ¼ 7 ms) for the Eu 3+ : 7 F 0 / 5 D 0 transition at 580 nm in 400 nm-diameter particles.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, annealing at high temperatures can improve the coherence properties and reduce the linewidths again to values less than 10 kHz, which is close to the bulk single crystal linewidth. In a further study on Tm 3+ ‐doped Y 3 Al 5 O 12 it was also found that mechanical treatment degrades the coherence properties of a material, whereas thermal annealing can improve them.…”
Section: Materials For Quantum Information Processingmentioning
confidence: 90%